ENERGIZERS AND THEIR USE IN SPEAKING LESSONS - Dilnoza Abduxoshimova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the role of energizers in enhancing speaking lessons in EFL/ESL (English as a Foreign Language / English as a Second Language) classrooms. Energizers are short, interactive activities that aim to increase learners’ engagement, motivation, and readiness to communicate in the target language. Drawing on communicative language teaching principles, the article highlights how energizers help reduce speaking anxiety, encourage active participation, and foster a supportive classroom atmosphere. Different types of energizers—physical, verbal, and cognitive—are discussed in relation to their contribution to fluency development and classroom interaction. The article concludes that the purposeful integration of energizers into speaking lessons can significantly improve learners’ oral communication skills and overall learning effectiveness.